Efficiency of Using the Reasil Humic Vet Feed Additive in Broiler Chicken Farming - Vyacheslavovich Korsakov, Konstantin; Alekseevich Vasiliev, Alexey; Pavlovich Moskalenko, Sergey; Alexandrovna Sivokhina, Lyubov; Yuryevich Kuznetsov, Maxim (International Journal of Engineering and Technology, 2018)
The research has shown the positive influence of the liquid water-soluble combined-effect feed additive Reasil Humic Vet, which consists of a concentrated solution of high-molecular sodium salts of humic acids extracted from leonardite, on the growth vigor, preservation rate and the quality of carcasses of broilers, and confirmed the appropriateness of its use in broiler poultry farming.Â Â